Evaluation of liquid and lyophilized preservatives for urine culture. - Weinstein, M P (1983)
Culture results of urine specimens transported conventionally (sterile cup) and in a commercial liquid or an investigational lyophilized preservative were compared in a hospital that experiences substantial delays in specimen transport to the laboratory (greater than 40% of specimens received after a delay of greater than or equal to 2 h). At the time of initial plating in the laboratory, 106 of 111 (95.5%) specimens that were positive (greater than or equal to 10(5) CFU of a single organism per ml in pure culture) after conventional transport were also positive in liquid preservative. After a 24-h holding period (cup refrigerated, preserved urine at room temperature), agreement was 91.4% (96 of 105). At the time of initial plating, agreement between results obtained by the conventional method and those obtained by using lyophilized preservative was 96.9% (63 of 65); after 24 h, agreement was 92.4% (61 of 67). Complete inhibition of growth of three Klebsiella pneumoniae isolates was observed in liquid preservative; however, urine processed in the lyophilized preservative did not show inhibition. The proportion of urine cultures showing no change in quantitative growth between the time of initial plating and repeat plating at 24 h was virtually identical for all three processing methods (83.6 +/- 0.9%). After the 24-h holding period, specimens processed in lyophilized preservative were less likely to show diminished quantitative growth than were specimens processed conventionally or in liquid preservative but were more likely to show an increase in growth of greater than or equal to 1 log. Nonetheless, the apparent lack of toxicity of lyophilized preservative may make it preferable to the currently available liquid preservative.